Perencanaan Kebutuhan Bahan Baku Guna Meningkatkan Efisiensi Produksi Batik Nambo Pada Rumah Industri Mutiara: Planning of Raw Material Requirements to Increase the Efficiency of Nambo Batik Production at Mutiara Industrial House - Yusnita Fitarini Sibay; Heny Ariwijaya (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2025)
The research was conducted at the Nambo Mutiara ikat and batik stamp industry, located in Nambo Bosa Village, Nambo District, Banggai Regency, Central Sulawesi. The purpose of the study was to determine the management of raw material inventory in order to increase the efficiency of Nambo batik production, using the Economic Order Quantity (EOQ) analysis method in determining the quantity of orders to be stored in the factory and the cost of orders to order the required inventory. The average raw material is IDR 50,000/cloth, dye IDR 1,200,000/package, wa/wax IDR 375,000/piece, with the cost components of ordering ship, bus, and courier costs amounting to IDR 520,000 per order, it is known that the number of raw material orders for a year is 1,116 pieces of cloth, 24 packages of dye, and 87 pieces of wax/wax. The calculation of the cost of ordering raw materials for a year is Rp6,240,000 for cloth, Rp6,240,000 for dye and Rp6,240,000 for wax = Rp28,134,961. The storage costs in the form of warehouse maintenance and electricity are Rp1,250,000, the calculation of the storage costs for raw materials is Rp58,125,000 for cloth, Rp1,250,000 for dye, and Rp4,531,250 for wax = Rp63,906,250. The results show that the total inventory costs that must be borne by the industrial house are Rp92,041,211. Controlling raw material inventory using the EOQ method, based on the calculation, the economic quantity for the order size for each type of raw material is 105 sheets of cloth, 15 dye packages, and 29 pieces of wax, with a lead time calculation for ordering is 12 days.